2015
DOI: 10.1111/tmi.12625
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of community‐based treatment for drug‐resistant tuberculosis in Bangladesh

Abstract: OBJECTIVE Drug-resistant tuberculosis (TB) threatens global TB control because it is difficult to diagnose and treat. Community-based programmatic management of drug-resistant TB (cPMDT) has made therapy easier for patients, but data on these models are scarce. Bangladesh initiated cPMDT in 2012, and in 2013, we sought to evaluate programme performance. METHODS In this retrospective review, we abstracted demographic, clinical, microbiologic and treatment outcome data for all patients enrolled in the cPMDT pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The importance of using appropriate screening tools for depression is highlighted in a recent review of community MDR-TB programmes in Bangladesh, where despite only 5% of cases having documented psychiatric symptoms in a chart review, once 60 patients were interviewed, 60% reported psychiatric symptoms. As interviews were not conducted by a psychiatrist, it is hard to determine the clinical significance of these symptoms, however the study does indicate potential missed opportunities for mental health treatment [15]. The limited but growing evidence base has raised the profile of treatment and support for depression within National TB programmes.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of using appropriate screening tools for depression is highlighted in a recent review of community MDR-TB programmes in Bangladesh, where despite only 5% of cases having documented psychiatric symptoms in a chart review, once 60 patients were interviewed, 60% reported psychiatric symptoms. As interviews were not conducted by a psychiatrist, it is hard to determine the clinical significance of these symptoms, however the study does indicate potential missed opportunities for mental health treatment [15]. The limited but growing evidence base has raised the profile of treatment and support for depression within National TB programmes.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of using appropriate screening tools for depression is highlighted in a recent review of community MDR-TB programmes in Bangladesh, where despite only 5% of cases having documented psychiatric symptoms in a chart review, once 60 patients were interviewed, 60% reported psychiatric symptoms. As interviews were not conducted by a psychiatrist, it is hard to determine the clinical signi cance of these symptoms, however the study does indicate potential missed opportunities for mental health treatment (15). The limited but growing evidence base has raised the pro le of treatment and support for depression within National TB programmes.…”
mentioning
confidence: 99%
“…A meta-analysis of MDR-TB patients found the median time when loss to follow-up occurred 7 months (IQR = 3-11) with the majority of loss to follow-up occurring in the initial phase of treatment (75% in the first 11 months) (14). The importance of using appropriate screening tools is highlighted in a recent review of community MDR-TB programmes in Bangladesh, where despite only 5% of cases having documented psychiatric symptoms in a chart review, once 60 patients were interviewed, 60% reported psychiatric symptoms (15). The limited but growing evidence base has raised the profile of treatment and support for depression within National TB programmes.…”
mentioning
confidence: 99%